HIIT-induced lactate/GPR81 signaling with dual branches converging on ERK1/2 contributes to hippocampal synaptic remodeling and memory improvement - Bian, Xuepeng; Shang, Qinghui; Zhu, Lutao; Liu, Jun; Wu, Min; Li, Jingjing; Lou, Shujie (Frontiers in Cell and Developmental Biology, 2026)
The remodeling of synapses in the hippocampus is intricately linked to processes of learning and memory. Research indicates that high-intensity interval training (HIIT) enhances cognitive functions reliant on the hippocampus in mice, although the specific receptor-mediated molecular pathways involved are not fully elucidated. Lactate, which is produced in significant amounts during HIIT, may function as a signaling agent in the brain through the lactate receptor G protein-coupled receptor 81 (GPR81), classified as a Gi-type G protein-coupled receptor. This investigation focused on the lactate/GPR81 pathway’s contribution to synaptic remodeling in the hippocampus induced by HIIT and examined its downstream signaling characteristics. In vivo results demonstrated that HIIT led to an increase in dendritic spine density and presynaptic vesicle density, enhancing learning and memory; however, these structural and cognitive improvements were negated by the knockdown of GPR81 in the hippocampus. In vitro experiments with Neuro-2a (N2a) cells, when treated with a GPR81 agonist alongside an adenyl cyclase (AC) agonist, a phospholipase C (PLC) inhibitor, and an extracellular signal-regulated kinase 1/2 (ERK1/2) inhibitor, revealed that GPR81 activation resulted in elevated ERK1/2 phosphorylation and increased levels of proteins associated with synaptic remodeling. Further pharmacological interventions reinforced a dual downstream signaling mechanism that involves the inhibition of the AC pathway and the activation of the PLC pathway, both of which converge on ERK1/2. Overall, these results suggest that the lactate/GPR81 pathway is essential for the critical aspects of HIIT-induced synaptic remodeling in the hippocampus and the enhancement of memory, supporting a GPR81-dependent dual-branch model that converges on ERK1/2 in a simplified in vitro context.